Islamic Shari'a Politics and Teungku Dayah's Political Authority Crisis in Aceh - NIRZALIN, NIRZALIN (Universitas Muhammadiyah Yogyakarta, 2012)
This study examines the Islamic Shari’a politics and Teungku Dayah’s political authority crisis inAceh. The main question being answered is how Islamic shari’a is adopted and practiced by thegovernment of Aceh and why Teungku Dayah as traditional Islamic leaders in Aceh did not becomethe dominant actor and even their political authority those who have been in crisis since the latter partof the New Order era not yet recovered in the political structure that has turned into all-Islam in thepost Order Baru.The result of this study indicate that the presence of Islamic shari’a in Aceh in thePost New Order cannot be utilized by Teungku Dayah to recover their political authority that hasbeen in crisis since the latter part of the New Order era. Because as a political formula that is intendedto reduce conflict, Islamic shari’a in Aceh since the first fully controlled by the state, bureaucraticallymanaged and modified for the benefit of the ruling power elite. As a result, the political authority ofthe Teungku Dayah in Aceh on post-New Order era did not recover from but remained as in theprevious era. However, Teungku Dayah’s political authority crisis in Aceh was not followed by a crisisof authority in the realm of religion. This fact emphasizez that Teungku Dayah’s political andreligious authority in Aceh which is previously integrated have now been separated.